(untitled) (Research, Society and Development, 2021)
Schizophrenia is a complex psychiatric disorder that begins early in an individual’s life and presents several social and cognitive deficits characterized by distortions of thought, self-perception, delusions, hallucinations, psychosis, and external reality. The objective was to analyze the actions developed by nurses in the Psychosocial Care Centers CAPS aimed at the permanence of the schizophrenic patient in treatment. An integrative literature review study was carried out with several searches in the databases Virtual Health Library (VHL), BDENF, LILACS, and SCIELO, with the descriptors: "Nurse", "Schizophrenia", and "CAPS". A total of 305 articles were selected, and after the inclusion and exclusion criteria were applied, 31 articles were selected for reading. After reading, 7 articles were selected that met the research objective. The results of the sample showed that the existing actions are constantly being improved and new strategies are being developed to keep the patient in the treatment. It is concluded that the nurse stands out in the care provided to the user with schizophrenia in health services, due to the bond established and responsibility in the structuring of strategies for the promotion of mental health.